High-speed treatment of low strength domestic wastewater for irrigation water production in pilot-scale classical, moving bed and fixed bed hybrid MBRs - Tuluk, Banu; Yildiz, Ergun; Nuhoglu, Alper; Tataroglu, Numan Suadi; Gulluce, Ekrem; Cengiz, Ibrahim; Degermenci, Nejdet; Angin, Ilker (Elsevier BV, 2022)
To evaluate the treatability of domestic wastewater under conditions of low hydraulic retention time and high organic loadings, 3 pilot-scale automatically controlled membrane bioreactors (MBRs) as classical (C-MBR), moving bed (MB-MBR), and fixed bed (FB-MBR) were established and operated for a total of 268 days. Estab-lished pilot plants were compared in terms of treatment performance, membrane fouling, irrigation water criteria, and power consumption values. Results obtained have shown that all three systems were able to achieve more than 93% removal of chemical oxygen demand (COD) in an average hydraulic retention time (HRT) of 1 hour, and MB-MBR and FB-MBR were superior in terms of total nitrogen (TN) and total phosphorus (TP) re-movals. It has been determined that MB-MBR and FB-MBR are also advantageous in terms of power consumption. Especially it has been found that FB-MBR can produce better quality irrigation water with 40% lower power consumption than C-MBR under the same conditions. It was concluded that biofilm-supported hybrid systems could be a practical application in the fight against increasing water scarcity and global warming, both in obtaining clean water with less power consumption and in protecting human and environmental health.
Keywords: Moving bed; Wastewater recovery; Irrigation water production; Membrane bioreactor; 13. Climate action; 7. Clean energy; 6. Clean water; 12. Responsible consumption